الرقيق CdO تأثير التعرض لجسيمات ألفا عمى الخواص البصرية لمغشاء - عزيز, أسماء أحمد (Al-Nahrain Journal of Science, 2012)
In this research, study effect of radioactive dose for Alpha-practical, by using radioactive source of (Am241), which has energy (5.49) MeV and activity of 76 KBq on optical Properties of thin film Cadmium oxide (CdO) which prepared by chemical spray pyrolysis.This research concerned with the study of the optical properties (energy gap, absorption coefficient, reflectance and extinction coefficient).The CdO thin films were evaluated spetrophoto metrically irradiated with Alpha-practical with doses of values )135, 410, 1100, 5500) rad. The energy gap was calculated before irradiation (2.38)eV and after irradiation (2.34, 2.22, 2.20,1.98) eV in respectively . The results showed decreasing in energy gap with absorbed dose there were light changes in other properties where as sign fiction changes, and considerable increments values of these properties in dose (5500)rad.